Healthy and diabetic primary human osteoblasts exhibit varying phenotypic profiles in high and low glucose environments on 3D-printed titanium surfaces - Allen, Nicholas; Aitchison, Alexandra Hunter; Abar, Bijan; Burbano, Julian; Montgomery, Mark; Droz, Lindsey; Danilkowicz, Richard; Adams, Samuel (Frontiers in Endocrinology, 2024)
ABSTRACT Background The revolution of orthopaedic implant manufacturing is being driven by 3D printing of titanium implants for large bony defects such as those caused by diabetic Charcot arthropathy. Unlike traditional subtractive manufacturing of orthopaedic implants, 3D printing fuses titanium powder layer-by-layer, creating a unique surface roughness that could potentially enhance osseointegration. However, the metabolic impairments caused by diabetes, including negative alterations of bone metabolism, can lead to nonunion and decreased osseointegration with traditionally manufactured orthopaedic implants. This study aimed to characterize the response of both healthy and diabetic primary human osteoblasts cultured on a medical-grade 3D-printed titanium surface under high and low glucose conditions. Methods Bone samples were obtained from six patients, three with Type 2 Diabetes Mellitus and three without. Primary osteoblasts were isolated and cultured on 3D-printed titanium discs in high (4.5 g/L D-glucose) and low glucose (1 g/L D-Glucose) media. Cellular morphology, matrix deposition, and mineralization were assessed using scanning electron microscopy and alizarin red staining. Alkaline phosphatase activity and L-lactate concentration was measured in vitro to assess functional osteoblastic activity and cellular metabolism. Osteogenic gene expression of BGLAP, COL1A1, and BMP7 was analyzed using reverse-transcription quantitative polymerase chain reaction. Results Diabetic osteoblasts were nonresponsive to variations in glucose levels compared to their healthy counterparts. Alkaline phosphatase activity, L-lactate production, mineral deposition, and osteogenic gene expression remained unchanged in diabetic osteoblasts under both glucose conditions. In contrast, healthy osteoblasts exhibited enhanced functional responsiveness in a high glucose environment and showed a significant increase in osteogenic gene expression of BGLAP, COL1A1, and BMP7, and a trend toward increased mineralization (p<.05). Conclusion Our findings suggest that diabetic osteoblasts exhibit impaired responsiveness to variations in glucose concentrations, emphasizing potential osteoblast dysfunction in diabetes. This could have implications for post-surgery glucose management strategies in patients with diabetes. Despite the potential benefits of 3D printing for orthopaedic implants, particularly for diabetic Charcot collapse, our results call for further research to optimize these interventions for improved patient outcomes. KEYWORDS: diabetes, Charcot, 3D printing, osteointegration, implants, additive manufacturing, BGLAP, BMP7, COL1A1.